Community Adaptation in Facing Environmental Pollution Challenges in the Industrial Designated Area of Lamongan Regency, East Java, Indonesia - Nafisah, Durrotun; Dellarosa, Maretha; Asnimawati; Samosir, Frans Judea (Journal of Social Dynamics and Governance, 2024)
Industrial growth is an opportunity for economic growth, but also a challenge for the environment, especially pollution from industrial waste. The purpose of the current research is to analyze community adaptation to the challenges of industrial environmental pollution. This research uses a qualitative phenomenological method. This study is located in Rejosari Village, Deket District, Lamongan Regency. The informants in this study include the main informant and supporting informants, totaling 29. Data collection included in-depth interviews, observations, and document studies. The data’s validity was tested through theoretical and source triangulation. The data analysis technique uses the interactive model of Miles & Huberman and NVivo 12. The study’s results show that community adaptation involves several parties, namely the government, industry, and society. The government manages and protects the environment, industry conducts proper waste treatment, and the public has a high level of environmental awareness. Collaborative Governance is used to manage environmental pollution caused by industrial waste.